Adsorption of 2-propanol on MgO Surface: A Combined Experimental and Theoretical Study - Fuente, Silvia Andrea (2014)
The adsorption of 2-propanol (or isopropanol) on MgO was studied using infrared (IR) spectroscopy and density functional theory (DFT) simulations. The analysis of IR spectra indicates that the molecule can adsorb either molecularly or dissociatively. DFT calculations show that the adsorption mode depends on the active site of the catalyst. While on perfect terrace it adsorbs non-dissociatively, on edge and on three-fold coordinated O anion (O-corner sites) the adsorption occurs dissociatively by breaking the O-H bond without activation barrier giving 2-propoxide and a surface hydroxyl group. Calculations also suggest that vacant oxygen centers on terrace, edge and corner are also possible sites for non-dissociative adsorption. On Mg ions located at corners the adsorption is strong but non-dissociative, while on a Mg vacancy at the same position the molecule easily dissociates. Frequency modes are also calculated and compared in detail with experimental IR spectra.